2014
DOI: 10.1080/01635581.2014.922201
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Black Raspberry Extracts on MnSOD Activity in Protection Against Concanavalin A Induced Liver Injury

Abstract: Inflammation and oxidative stress are the key events in carcinogenetic transformation. Black raspberries (BRB) have been demonstrated to have antioxidant, anti-inflammatory and anti-cancer bioactivities. In this study, a concanavalin A induced hepatitis mouse model is used to examine the effect of BRB extract on hepatic injury. Three BRB extracts, including ethanol/H2O extracts (both anthocyanin-contained fraction and non-anthocyanin-contained fraction) and hexane extract were used. The alterations in hepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…A similar effect was observed in infections caused by influenza A virus where inclusion of MnSOD in aerosols led to a mild improvement of the disease. Other natural antimicrobials are also known for their antioxidant effect 12 also when included in the feed of farmed poultr 34 with a direct effect in controlling the levels of MnSOD 35 .…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect was observed in infections caused by influenza A virus where inclusion of MnSOD in aerosols led to a mild improvement of the disease. Other natural antimicrobials are also known for their antioxidant effect 12 also when included in the feed of farmed poultr 34 with a direct effect in controlling the levels of MnSOD 35 .…”
Section: Discussionmentioning
confidence: 99%
“…A volume of 10 μL of sample or standard was added to 200 μL of diluted “radical detector” in a 96‐well plate. Addition of 1 mmol/L potassium cyanide (KCN) was used to block Cu/Zn‐SOD and extracellular SOD activity, resulting in detection of only Mn‐SOD activity in samples (Li et al ). Reactions were initiated by adding 20 μL of supplied xanthine oxidase using a multichannel pipette.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous reports have revealed potential therapeutic approaches to improve Con A-induced liver injury through suppression of oxidative stress and apoptotic cell death 34 36 . Our results indicated that the MDA level was significantly increased in the aged mice compared with that of the young mice, and a further elevation was observed in aged mice after Con A challenge (Fig.…”
Section: Resultsmentioning
confidence: 99%